2022
DOI: 10.1128/spectrum.02593-21
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Endotype-Associated Airway Resistome in Chronic Obstructive Pulmonary Disease

Abstract: Antibiotics are commonly prescribed for both acute and long-term prophylactic treatment in chronic airway disorders, such as chronic obstructive pulmonary disease (COPD), and the rapid growth of antibiotic resistance is alarming globally. The airway harbors a diverse collection of microorganisms known as microbiota, which serve as a reservoir for antibiotic resistance genes or the resistome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…With the growth of age, the incidence of many lung diseases is also gradually increasing, among which chronic obstructive pulmonary disease and pulmonary fibrosis are the most significant [ 47 ]. At present, some progress has been made in the relationship between aging, and chronic obstructive pulmonary disease and pulmonary fibrosis [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the growth of age, the incidence of many lung diseases is also gradually increasing, among which chronic obstructive pulmonary disease and pulmonary fibrosis are the most significant [ 47 ]. At present, some progress has been made in the relationship between aging, and chronic obstructive pulmonary disease and pulmonary fibrosis [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of antibiotics is particularly prevalent in COPD, especially in primary health care who receive three times more antibiotic prescriptions than general population [43]. The accompanying rapid growth of antibiotic resistance is a health challenge [27]. The maintenance treatment with macrolide antibiotics has been proved to be effective in reducing exacerbations in COPD [44], but long-term macrolide therapy contributes to antibiotic resistance [45].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of antibiotic resistance genes before and after PR Antibiotics are commonly prescribed for the treatment of acute exacerbations of COPD, accompanied by the increased risk of antibiotic resistance in the COPD patients [27]. In view of this situation, we analyzed the resistance genes of respiratory microbiome before and after 2-week PR.…”
Section: Alterations Of Respiratory Microbiome Function Before and Af...mentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD) is a heterogeneous disease related to inflammation and the source of heterogeneity is related to the inflammatory endotypes involved in neutrophils and eosinophils [27].More and more studies have shown that N6 adenosine methylation (m6A) is the most common RNA regulator, which can modify the epigenetics of proteins [28].However, the mechanism of m6A methylation regulator in COPD is not clear. Therefore, this study explored the relationship between the gene expression matrix of COPD in GEO database and m6A typing and immune cell infiltration by using R software.…”
Section: Discussmentioning
confidence: 99%